Hearts from mice fed a non-obesogenic high-fat diet exhibit changes in their oxidative state, calcium and mitochondria in parallel with increased susceptibility to reperfusion injury. - Ben Littlejohns; Philippe Pasdois; Simon Duggan; Andrew R Bond; Kate Heesom; Christopher L Jackson; Gianni D Angelini; Andrew P Halestrap; M-Saadeh Suleiman (PLoS ONE)
Rationale High-fat diet with obesity-associated co-morbidities triggers cardiac remodeling and renders the heart more vulnerable to ischemia/reperfusion injury. However, the effect of high-fat diet without obesity and associated co-morbidities is presently unknown. Objectives To characterize a non-obese mouse model of high-fat diet, assess the vulnerability of hearts to reperfusion injury and to investigate cardiac cellular remodeling in relation to the mechanism(s) underlying reperfusion injury. Methods and results Feeding C57BL/6J male mice high-fat diet for 20 weeks did not induce obesity, diabetes, cardiac hypertrophy, cardiac dysfunction, atherosclerosis or cardiac apoptosis. However, isolated perfused hearts from mice fed high-fat diet were more vulnerable to reperfusion injury than those from mice fed normal diet. In isolated cardiomyocytes, high-fat diet was associated with higher diastolic intracellular Ca2+ concentration and greater damage to isolated cardiomyocytes following simulated ischemia/reperfusion. High-fat diet was also associated with changes in mitochondrial morphology and expression of some related proteins but not mitochondrial respiration or reactive oxygen species turnover rates. Proteomics, western blot and high-performance liquid chromatography techniques revealed that high-fat diet led to less cardiac oxidative stress, higher catalase expression and significant changes in expression of putative components of the mitochondrial permeability transition pore (mPTP). Inhibition of the mPTP conferred relatively more cardio-protection in the high-fat fed mice compared to normal diet. Conclusions This study shows for the first time that high-fat diet, independent of obesity-induced co-morbidities, triggers changes in cardiac oxidative state, calcium handling and mitochondria which are likely to be responsible for increased vulnerability to cardiac insults.